Program Kemitraan Masyarakat (PKM) Pengembangan Desa Wisata di Desa Sitiluhur Kecamatan Gembong Kabupaten Pati - Donny Anhar Fahmi; Muh. Isna Nurdin Wibisana; Rosalina Ginting; Dani Slamet Pratama; Rahmat Hidayat (Universitas Islam Nahdlatul Ulama Jepara, 2018)
Abstrak Sitiluhur Village, Gembong Sub-district, Pati Regency has good tourism potential, but the local people have not realized this yet. This is based on a survey team of students of KKN University of PGRI Semarang. The purpose of activities is (1) to give directions to tourism place in Sitiluhur village, (2) development of tourism potency, (3) community empowerment of Sitiluhur village. This devotional activity was held with Partners from residents in Sitiluhur Village, Gembong Sub-district, Pati Regency. The method used is the method of supporting tourism analysis, object analysis methods, methods of tourism attraction analysis. The result of this is able to maximize the existing tourism potential. Procurement directions to the place of tourism, addition of places for selfie in Kebo Amuk Waterfall (Tedunan) for tourist attractions more interested tourists, making a bridge of love from wood to cross in Kebo Amuk Waterfall. Conclusion of the socialization of the importance of community empowerment and ‘pokdarwis’ Sitiluhur Village for people aware of tourism potential. Such efforts are aimed at popularizing the village of Sitiluhur as a Tourism Village as well as in the future able to increase the economic growth of local communities.